The amount of available food affects diurnal locomotor activity in migratory songbirds during stopover - Ferretti, Andrea (Sci Rep, 2019)
Migratory passerine birds fly long distances twice a year alternating nocturnal flights with stopovers to rest and replenish energy stores. The duration of each stopover depends on several factors including internal clocks, meteorological conditions, and environmental factors such as availability of food. Foraging entails energetic costs, and if birds need to refuel efficiently, they should modulate their activity in relation to food availability. We investigated how food availability influences locomotor activity in migrating birds of six passerine species at a spring stopover site in the central Mediterranean Sea. We selected birds with low fat scores which we expected to be strongly motivated to refuel. We simulated stopover sites of different quality by providing temporarily caged birds with different amounts of food to simulate scarce to abundant food. We analysed the diurnal locomotory activity as a proxy for food searching effort. Low food availability resulted in an increased diurnal locomotor activity in almost all species, while all birds showed low intensity of nocturnal migratory restlessness. In conclusion, our study shows that food availability in an important determinant of behaviour of migratory birds at stopover sites.